A comparative analysis of gene expression among castes of the termite Reticulitermes flavipes using expressed sequence tags (ESTs) and a microarray - Steller, Matthew Michael (Kansas State University, 2009)
Termites (Isoptera) are separated into morphologically and behaviorally specialized castes of sterile workers and soldiers, and the reproductive alates. Previous research on eusocial insects has indicated that caste differentiation has a genetic basis. Although much has been studied about the genetic basis of caste differentiation and behavior in the honey bee, Apis mellifera, termites remain comparatively understudied. Therefore, my objective was to compare the gene expression patterns of different castes of the termite Reticulitermes flavipes based on EST analyses and a microarray. Soldier, worker, and alate caste and two larval life stage cDNA libraries were constructed, and ~15,000 randomly chosen clones were sequenced to compile an EST database. Putative gene functions were assigned based on a BLASTX Swissprot search. Categorical expression patterns for each library were compared using the in silico methods of BLAST2GO and r-statistics. I chose 2,240 unique-ESTs based on their putative function and sequence quality, which I used to fabricate a Combimatrix microarray. I used the microarray to compare expression levels between workers and soldiers from Kansas and Florida populations. Seventy to ninety percent of the sequences from the ESTs of each caste and life stages had no significant similarity to those in existing databases. All libraries contained sequences with putative reproductive functions, which was unexpected in the non-reproductive soldier and worker castes. Sequences of interest that showed a putative bias among castes include a viral protein in soldiers and a possible chemosensory protein in alates, which may be involved in termite reproductive functionality or communication. The microarray showed increased expression in the soldier caste of a sequence that matched tropomyosin and an increased expression level of a sequence that matched a PDZ-domain containing protein in some worker samples. This study leads to several candidate genes of potential caste specific function, which can be further tested using functional analysis and between the different castes and life stages of R. flavipes. These genes include the sequences similar to pebIII and RGS-GAIP. I have also expanded upon the available sequences for this termite and utilized the r-statistic in silico method for the first time to putatively compare gene expression in the different castes of a eusocial insect. The in silico analysis allowed us to identify several genes which may show biased expression patterns in the different cDNA libraries and which may reveal caste-specific expression controlling important functions after further analysis. These candidates include: an alate-biased gene, which had a predicted function of neurotransmitter secretion and cholesterol absorption as well as a late larval-biased gene which was predicted to be involved in protein biosynthesis and ligase activity.
Keywords: Sociogenomics; Bioinformatics; R-statistics; Genome; Biology, Entomology (0353); Biology, General (0306)